Can we resolve the pesticide quandary with eco-efficiency metrics? - Kreick, Liz; Magarey, Roger D.; Love, Madison; Carley, Danesha Seth (Frontiers in Agronomy, 2025)
More than fifty years after the publication of Silent Spring, the United States continues to struggle with balancing the benefits of pesticide use against their environmental and public health costs. These costs are also known as pesticide externalities because these are paid by society at large rather than factored into the costs of production. A major contributing factor to this imbalance is the absence of standardized, widely adopted metrics and tools for assessing and reducing pesticide externalities in day-to-day agricultural production and urban pest management. This leaves producers, consumers, and policymakers without clear guidance for decision-making. Researchers are also impacted, left without coordinated direction or incentives to focus their work on the reduction of pesticide externalities. This has contributed to what we call the Pesticide Quandary: a social-ecological trap in which dependence on chemical controls perpetuates feedback loops of increasing pesticide resistance and pesticide externalities. Addressing this systemic challenge requires rethinking how policies, incentives, and research agendas align to break out of this trap. Historically, Integrated Pest Management (IPM) was promoted as a strategy to mitigate the Pesticide Quandary with some notable success stories. However, a lack of clear metrics to measure IPM’s impact on pesticide externalities has limited federal support for IPM adoption by producers and also funding for IPM research and Extension. Eco-efficiency offers a potential solution to the Pesticide Quandary by tracking and incentivizing IPM practices that reduce pesticide externalities while sustaining agricultural productivity. Eco-efficiency is a strategy used to improve environmental outcomes in a variety of industries. A simple eco-efficiency score can be calculated from the productivity of a crop divided by the total toxicity of the pesticides applied. An eco-efficiency framework offers a standardized method for quantifying, tracking and incentivizing increased productivity and reductions in environmental and human health externalities from pesticides and improvements in productivity. Key recommendations include the development of standardized eco-efficiency scoring systems, their integration into decision support tools, and regulatory policies that encourage the adoption of sustainable pest management practices. This analysis underscores the need for measurable, incentive-driven frameworks to break the negative feedback cycle of the Pesticide Quandary and promote long-term sustainability in agricultural and urban systems.